Penggunaan Azospirillum pada Tanah Masam dengan Aluminium Tinggi Terhadap Produksi dan Serapan Nitrogen Rumput Setaria splendida dan Chloris gayana - P.D M.H Karti (Media Peternakan, 2005)
High content of Al on the soil maybe harmful (toxic for plant). Red and yellow podzolic soil was marginal land that characterized by high Al content. Azospirillum is free living N fixing bacteria that can be associated with grass. This research was conducted to find the best yield of grass planted on the soil inoculated with Azospirillum. The research consisted of some steps; 1) soil sampling 2) laboratory research: bacterial isolation, isolate selection, standardized of population, content of IAA 3) pod experiment. Pod experiment in the glass house was designed in completely randomized design, that consisted of six treatments. The variables observed were dry mass production of shoot and root, nitrogen content of shoot and root, and nitrogen absorption. Four best isolates chosen were; SM Setaria, OBIS/BD, PO2 and PM2. Azospirillum isolates enhanced shoot and root production, nitrogen content and N total absorption of tolerance one (S. splendida). The susceptible (C. gayana), Azospirillum significantly enhanced shoot and root nitrogen content, but did not affect the growth, production and N total absorption. Root growth that was inhibited by Al toxicity, decreased the symbiotic capability of nitrogen fixing bacteria. PM2 isolate showed the best effect on production and quality of S. splendida as well as on C. gayana. This isolate will be used for future research. PM2 produces 6.4 ppm Indole Acetic Acid that promoted root growth. Key words: Azospirillum sp, Setaria splendida, Chloris gayana, Al toxicity